VD_FINDINFO Jug / 2013 / 128 vom 25. September 2012 - VD Tribunal cantonal (2012)
PEINE, PRÉTENTION DE DROIT PUBLIC, DISPOSITIONS PÉNALES DE LA LSTUP | 40 CP, 43 CP, 44 CP, 49 al. 1 CP, 49 al. 2 CP, 49 CP, 71 CP